Knowing the unknown: The underestimation of monkeypox cases. Insights and implications from an integrative review of the literature - Bragazzi, Nicola Luigi; Woldegerima, Woldegebriel Assefa; Iyaniwura, Sarafa Adewale; Han, Qing; Wang, Xiaoying; Shausan, Aminath; Badu, Kingsley; Okwen, Patrick; Prescod, Cheryl; Westin, Michelle; Omame, Andrew; Converti, Manlio; et al. (Frontiers in Microbiology, 2022)
Monkeypox is an emerging zoonotic disease caused by the monkeypox virus, which is an infectious agent belonging to the family of Poxviruses. Currently, commencing from the end of April 2022, an outbreak of monkeypox is ongoing, with more than 25,000 cases being reported as of August 3, 2022, involving 90 countries and territories across all the six World Health Organization (WHO) regions. On July 23, 2022, the Director-General of the WHO declared monkeypox a global public health emergency of international concern (PHEIC), since the outbreak represents an extraordinary, unusual and unexpected event with poses a significant risk for international spread, requiring an immediate, coordinated international response. The real magnitude of such a burden could be masked by a certain degree of uncertainty due to the failure of capturing all cases, with a portion of them remaining underestimated. As such, underestimation affects the efficiency and reliability of surveillance and notification systems and compromises the possibility of making informed and evidence-based policy decisions in terms of the adoption and implementation of ad hoc adequate preventive measures. In this paper, synthesizing 53 papers, we review the determinants of the underestimation of a sexually transmitted disease, and, in particular, monkeypox, in terms of all its various components and dimensions (under-ascertainment, underreporting, under-detection, under-diagnosis, misdiagnosis/misclassification, and under-notification).